1997
DOI: 10.1002/(sici)1097-0010(199712)75:4<489::aid-jsfa902>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen on acetic acid production by Brettanomyces/Dekkera in winemaking

Abstract: :Since the large occurrence of Brettanomyces yeasts in strict anaerobiosis environments (sparkling wines) has been found without an increase in acetic acid content, we evaluated the inÑuence of the oxygen concentration on acetic acid production. Results showed that the oxygen concentration exerted a strong inÑuence on both growth and acetic acid production by Brettanomyces yeasts in winemaking. Full aerobiosis lead to a large production of acetic acid causing a block of metabolic activity. Semi-aerobiosis resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 0 publications
5
45
1
Order By: Relevance
“…These observations suggested that the presence of acetic acid is not the only cause of inhibition of glucose metabolism and growth; the concomitant presence of acetic acid and oxygen mainly exerts a negative effect on both. As expected, oxygen limitation inhibited acetic acid production in the control cultures because its production is associated with oxygen concentration (41). Nevertheless, the presence of acetic acid in the growth medium stimulated its biosynthesis instead of its consumption (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggested that the presence of acetic acid is not the only cause of inhibition of glucose metabolism and growth; the concomitant presence of acetic acid and oxygen mainly exerts a negative effect on both. As expected, oxygen limitation inhibited acetic acid production in the control cultures because its production is associated with oxygen concentration (41). Nevertheless, the presence of acetic acid in the growth medium stimulated its biosynthesis instead of its consumption (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have shown that the availability of oxygen presents a favourable scenario for the development of Brettanomyces/Dekkera yeasts during winemaking as it supports their growth and survival and also acetic acid production (Ciani et al, 1997;Freer et al, 2003;Aguilar-Uscanga et al, 2003). In contrast, anaerobosis during alcoholic fermentation may well impede Brettanomyces/Dekkera growth, but would not necessarily prevent their development (Ciani et al, 1997).…”
Section: Volatile Acidity (Va) and Other Volatile Fatty Acidsmentioning
confidence: 99%
“…under both aerobic and semi-aerobic conditions 12,16 . Cotton-plugged and shake flask fermentations would be considered as micro-aerobic, resulting in favourable conditions for ethanol reduction and acetic acid production 5 . But in this case, ethanol analysis (data not shown) showed that ethanol was consumed by all the strains in the second part of fermentation (13 to 25 g/L) without any correlation to the second growth phase when it existed.…”
Section: -Ethylphenol Profilesmentioning
confidence: 99%